2015
DOI: 10.1016/j.trci.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic brain injection of human umbilical cord blood mesenchymal stem cells in patients with Alzheimer's disease dementia: A phase 1 clinical trial

Abstract: IntroductionWe conducted a phase 1 clinical trial in nine patients with mild-to-moderate Alzheimer's disease to evaluate the safety and dose-limiting toxicity of stereotactic brain injection of human umbilical cord blood–derived mesenchymal stem cells (hUCB-MSCs).MethodsThe low- (n = 3) and high-dose (n = 6) groups received a total of 3.0 × 106 cells/60 μL and 6.0 × 106 cells/60 μL, respectively, into the bilateral hippocampi and right precuneus.ResultsNo patient showed serious adverse events including fever d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 31 publications
5
120
0
1
Order By: Relevance
“…[34][35][36][37] Therefore, umbilical cord cells exhibit significant clinical benefits, including their ease of accessibility and regenerative capacities. Therefore, the effect of huMSCs on T cell-mediated immunity was examined by severe acute graft-versus-host disease (www.clinicaltrials.gov).…”
Section: Levels Of Cytokines Measured By Rt-qpcr and Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] Therefore, umbilical cord cells exhibit significant clinical benefits, including their ease of accessibility and regenerative capacities. Therefore, the effect of huMSCs on T cell-mediated immunity was examined by severe acute graft-versus-host disease (www.clinicaltrials.gov).…”
Section: Levels Of Cytokines Measured By Rt-qpcr and Elisamentioning
confidence: 99%
“…severe acute graft-versus-host disease (www.clinicaltrials.gov). [34][35][36][37] Therefore, umbilical cord cells exhibit significant clinical benefits, including their ease of accessibility and regenerative capacities.…”
Section: Levels Of Cytokines Measured By Rt-qpcr and Elisamentioning
confidence: 99%
“…[11][12][13] Recently numerous clinical trials have shown that naive human mesenchymal stem cells (MSCs) are safe and beneficial to be considered for design of treatment methods for various pathologies. [14][15][16] The primary mechanism of their therapeutic effects is via secretion of paracrine factors under abnormal and diseased cellular environments. For example, the paracrine action of human MSC has been demonstrated to prevent cell death and induce proliferation of endogenous progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The preclinical data on MSCs both alone and in conjunction with other treatment strategies are promising. These cells have entered at least Phase I (safety) clinical trials for multiple nervous system diseases and injuries, most notably cerebral ischemia, multiple sclerosis, Alzheimer's disease, and TBI . While we have a better understanding of the pathologic cascades triggered after TBI and the mechanisms by which MSCs repair the brain and improve functional outcomes, we are still years away from realizing an effective regenerative medicine therapy for TBI that is widely available to patients.…”
Section: Resultsmentioning
confidence: 99%